Relative income change and pro-poor growth - Marek Kośny; Gastón Yalonetzky (Luxembourg Income Study (LIS), 2015)
Most methods for the analysis of distributional change rely on the changes in the income of a particular group of people, taking either the situation of this group in the previous period, or the average change in the population, as reference point. By contrast, we propose a measure of distributional change based on the comparison of a group's wellbeing standard against a richer group, thereby capturing a notion of change in relative income, which embodies the influence of others' wellbeing on the judgment of the group's own situation. The indices, and related relative income change (RIC) curves, are based on ratios of generalized mean incomes between two groups, which render them closely related to Zenga's inequality measures and Lorenz curve comparisons, when arithmetic means are used. We consider both relative and absolute income cut-offs for the group partitions. Differences and similarities between our measures of relative income change and the Growth Incidence Curve are also discussed. These are highlighted in an empirical illustration on European countries.
Keywords: I31; J30; 330; relative income; income distribution; pro-poor growth